NUTRITION AND ENDOTHELIAL FUNCTION: A REVIEW OF KETOGENIC AND PLANT-BASED DIETARY INTERVENTIONS - Agata Ogorek,; Dominika Ziolkowska,; Julia Andrzejewska,; Julianna Zielska,; Eliza Gawron,; Michał Ziemba,; Paweł Liszka,; Marcin Kapij,; Klaudia Zackiewicz,; Aleksandra Kaniak, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Endothelial function is crucial for maintaining vascular homeostasis by regulating vasomotor tone, inflammation, and immune responses. Impairment of endothelial function is an early indicator of cardiovascular disease (CVD). Given the increasing prevalence of CVD, identifying modifiable risk factors, including dietary patterns, is becoming increasingly important.Aim of the study: This review compares the effects of ketogenic and plant-based diets on endothelial function, highlighting molecular mechanisms and clinical implications.Methodology: Literature was searched in PubMed, Scopus, and Web of Science (June–September 2025) using the keywords endothelium, ketogenic diet, vegetarian diet, atherosclerosis, and oxidative stress. Studies published in English between 2010 and 2025 were analyzed.Results: Ketogenic diets, although effective for weight loss, can lead to dehydration, micronutrient deficiencies, and increased endothelial inflammation due to low antioxidant intake. In contrast, plant-based diets are rich in fiber and antioxidants and low in trans fats, supporting endothelial integrity and reducing inflammation, though they may lack adequate EPA and DHA.